1967
DOI: 10.1111/j.2042-7158.1967.tb07986.x
|View full text |Cite
|
Sign up to set email alerts
|

The metabolism of ethionamide and its sulphoxide

Abstract: The fate of orally administered ethionamide (2‐ethyl‐4‐thiocarbamoylpyridine) and ethionamide sulphoxide in man, rats, mice and dogs has been examined. Though spontaneous interconversion between the two antituberculosis drugs does not take place, there was extensive interconversion in vivo, both appearing in the blood within 15 min of dosing irrespective of which compound was administered. Species differences were evident in both the rate of metabolism and in the ethionamide: ethionamide sulphoxide ratio. Apar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

1970
1970
2016
2016

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 33 publications
(11 citation statements)
references
References 10 publications
0
11
0
Order By: Relevance
“…34, 35 Ethionamide (2-ethylisothionicotinamide) and its S -oxide metabolite are likewise readily interconvertible in man, rats, mice and dogs. 36 The back reduction of TASO may have important consequences for the biology of liver injury by TA and TASO. Chilakapati et al 15, 28 administered [ 14 C]-TASO to rats and observed that a 12-fold increase in dose caused only a 2.5-fold increase in covalent binding to liver proteins.…”
Section: Discussionmentioning
confidence: 99%
“…34, 35 Ethionamide (2-ethylisothionicotinamide) and its S -oxide metabolite are likewise readily interconvertible in man, rats, mice and dogs. 36 The back reduction of TASO may have important consequences for the biology of liver injury by TA and TASO. Chilakapati et al 15, 28 administered [ 14 C]-TASO to rats and observed that a 12-fold increase in dose caused only a 2.5-fold increase in covalent binding to liver proteins.…”
Section: Discussionmentioning
confidence: 99%
“…Although activated ETA has been shown to share a common molecular target with INH, KatG mutants resistant to INH retain their sensitivity toward ETA, suggesting that ETA activation requires an entirely different enzyme. It has long been known that in vivo ETA demonstrates more consistent antitubercular activity than one would expect from in vitro examination of its minimal inhibitory concentration (MIC), and it has been demonstrated that a major metabolite of ETA in vivo is its S-oxide (2), which shows comparable in vitro activity (18)(19)(20)(21)(22). A wide variety of toxic thiocarbonyl-containing compounds have been shown to be converted to the corresponding S-oxides during in vivo metabolism by mammals supporting this as an intermediate oxidation in the metabolic activation of ETA (23).…”
mentioning
confidence: 99%
“…3A) (Vannelli et al, 2002). Assessment of biologic activity of the S-oxide metabolites showed that this metabolite retained full activity of ethionamide against Mycobacterium tuberculosis (Johnston et al, 1967). Similarly, human FMO1 and FMO3 have been shown to catalyze the oxidative activation of thiacetazone to isolable sulfinic acid and carbodiimide metabolites (Fig.…”
Section: Flavin-containing Monooxygenasesmentioning
confidence: 99%